Differential Diagnosis of Keratoconus Based on New Technologies - Sideroudi, Haris; Flockerzi, Elias; Seitz, Berthold (Klinische Monatsblätter für Augenheilkunde, 2022)
Keratoconus (KC) must be distinguished from other corneal ectatic diseases and thinning disorders for stage-appropriate and suitable management of each condition. The most relevant corneal pathologies that may imitate the tomographic KC pattern are pellucid marginal degeneration (PMD), keratoglobus, posterior keratoconus, and Fuchs-Terrien marginal degeneration (FTMD). In moderate cases of KC, differentiation is typically possible using slit lamp examination and corneal tomography with evaluation of the location of the corneal thinning region. In early cases, however, differential diagnosis may be more challenging since the cornea may look relatively normal. In severe cases, the extended area of corneal thinning also complicates differentiation. Biomicroscopic findings cannot always give all the information needed to distinguish KC from related ectatic corneal conditions. The aim of this work is to discuss contemporary techniques and findings to assist physicians to identify the correct diagnosis. Corneal topography has been used in recent decades as the main tool for imaging in ectatic corneal diseases. Moreover, Scheimpflug cameras (corneal tomographers), which analyze both anterior and posterior corneal surfaces, curvatures, pachymetry, elevation data, higher order aberrations, Fourier analysis of keratometric data, and corneal density have become the most promising tools for diagnosis and follow-up of ectatic diseases. A noninvasive air pulse tonometer in conjunction with an ultrahigh-speed Scheimpflug camera complements tomographic findings by analyzing biomechanical corneal properties. Α confocal microscopy system, which is a novel clinical technique for the study of corneal cellular structure, could contribute effectively in the same direction. Moreover, anterior segment optical coherence tomography (AS-OCT) creates cross-sections, which can be generated into a three-dimensional structure to produce corneal epithelial thickness (ET) measurements. ET mapping is increasingly recognized as a sensitive tool for the diagnosis of ocular surface disorders. Combining information of all these systems could lead to a more effective identification and differential diagnosis of ectatic corneal disorders.
Keywords: keratoconus; pellucid marginal degeneration; keratoglobus; posterior keratoconus; Fuchs Terrien marginal degeneration; differential diagnosis